Supramolecular Chemistry of Biomimetic Systems - Li, Junbai (Springer Singapore : Imprint: Springer, 2017)
This book investigates the latest developments in supramolecular assembly systems for mimicking biological structures and functions. Consisting of 14 chapters, it covers various assembly systems, such as polysaccharides, peptides, proteins, biopolymers, natural materials and various hybrid systems. Further, it focuses on different types of supramolecular systems with particular functions or structures that are relevant to living systems. A number of modern techniques used to study the supramolecular systems, such as total internal reflection fluorescence microscopy (TIRFM) and two-photon confocal microscopy, are also introduced in detail. Unlike conventional books on supramolecular assemblies, this book highlights the functions of the assembly systems, particularly their biological applications. As such, it offers a valuable resource for experienced researchers, as well as graduate students working in the field of supramolecular chemistry and biomimetic systems.
Keywords: Materials science.; Biomedical engineering.; Biomaterials.; Nanotechnology.; Materials -- Surfaces.; Thin films.; elektronické knihy; electronic books